Torque teno virus and hepatitis: a review on correlation - Hazanuddin, Siti Nurzulaikha; Sekawi, Zamberi; Yoke, Kqueen Cheah; Rasdi, Rasnaizam; Othman, Zulkefley (Biome Scientia, 2019)
Torque teno virus (TTV) is one of the “orphan” viruses that have been discovered almost two decades ago, with little information on the relationship of the infection to any diseases. It is one of the 45% of the commensal virus which is found throughout the population and becoming one of the most extensively studied viruses on its prevalence among the various level of health status. From healthy blood donors to patients who suffered severe illness, TTV infection level seems to be high and the findings have triggered interest from the researcher. Even though the study on TTV prevalence is actively performed, the actual pathogenesis of TTV to any specific diseases is yet to be ascertained. Many suggestions on the possible association of TTV infection with severe diseases such as acute respiratory diseases, liver-related diseases and even cancer have been discussed. However, one type of diseases which might have an association with TTV is hepatitis. Albeit, it remains a theory as the actual pathogenicity of TTV is not fully understood.